ANTHROPOMETRIC ASSESSMENT OF OBESITY AMONG IBD PATIENTS - Mirela Moneva; Antonia Atanassova (Science & Research)

(untitled)
The prevalence of obesity in IBD patients is a major research topic, showing a considerable variation in an incidence between 5 and 30%. The aim of the present study was to make an anthropometric assessment of obesity among IBD patients. Materials and methods: 50 IBD patients were studied. For each patient, data on age, gender, abdominal circumference, weight and BMI, smoking habits, and relevant comorbidities were collected. Obesity was diagnosed with a BMI > 30 kg/m2. The data were processed statistically using variation, dispersion, correlation and comparative analyses. Results: The percentage of men and women was even, with an average age of 43.26, a minimum age of 18, and a maximum age of 75. No difference in the age of onset was found between US and CD patients. The majority of the studied patients are genetically burdened with diabetes mellitus and hypertensive disease. The disease appears in younger patients having IBD and obesity. In conclusion, our study can lay the foundation of some further research. Because of the epidemiological increase of IBD in the developed countries, the pathogenetic role and influence on the disease outcome played by a diet should not be underestimated and should be further investigated. Planning new clinical trials aiming the evaluation of the clinical, laboratory and endoscopic parameters at baseline and after the changes in BMI may be useful, as this topic is still very poorly studied.